Collecting, extracting and storing web research survey questionnaires data - F. Dorneles, Carina; N. Mathias, Gilney (Journal of Information and Data Management, 2022)
Companies or institutions can use survey questionnaires to evaluate items or products, analyze their employees/customers’ satisfaction or collect any data they consider helpful. Furthermore, questionnaires can be used to collect data that can be used in research studies. Some problems in creating such questionnaires involve: deciding which questions to ask, how to ask them, and how to organize them. Many research communities, especially in the healthcare field, maintain repositories that are publicly accessible and include different questionnaires that help professionals and researchers analyze the results of questions, add new questions, or even point out nonsense questions. In this paper, we describe: (i) web crawler, which scans the Web searching for sites that possibly contain questionnaires; (ii) an extractor, which extracts the questionnaires from the list of pages collected by the crawler and saves them into a relational database; and (iii) the public dataset we have created to persist the questionnaires. The database created can then serve to analyze these data and/or as a centralized base of examples to prepare new questionnaires or reuse existing questions. The experiments we have conducted demonstrate that our crawler has achieved 94,47%, and the extractor has achieved a precision between 90% and 92%.